Ambient PM2.5 caused cardiac dysfunction through FoxO1-targeted cardiac hypertrophy and macrophage-activated fibrosis in mice. (May 2020) - Su, Xuan; Tian, Junzhi; Li, Binghua; Zhou, Lixiao; Kang, Hui; Pei, Zijie; Zhang, Mengyue; Li, Chen; Wu, Mengqi; Wang, Qian; Han, Bin; Chu, Chen; et al.
Abstract: Plenty of epidemiological evidences have shown that ambient particulate matter (PM2.5) exposure increased the prevalence of cardiovascular disease, but the potential mechanism has not been known clearly. We established mice models by ambient PM2.5 exposure system to explore the adverse effects of PM2.5 on cardiac function in mice. Forty-eight C57BL/6 mice were randomly divided into 3 groups and exposed to filtered air (FA), unfiltered air (UA) and concentrated PM2.5 air (CA) for 8 or 16 weeks, 6 hours per day, 7 days per week, respectively. The changes of cardiac structure and function, histological analysis and related mechanism were investigated. The main manifestations of cardiac structure were cardiac hypertrophy and fibrosis in a dose- and time-dependent manner after PM2.5 exposure, which led to the decrease of cardiac systolic function. Cardiac hypertrophy in mice might be regulated by PI3K/Akt/FoxO1 signal. Cardiac fibrosis might be attributed to inflammatory infiltration caused by macrophage activation. Consequently, our data indicated that cardiac hypertrophy and fibrosis might be important factors of PM2.5-induced cardiac dysfunction in mice. Graphical abstract: Image 1 Highlights: Real-time PM2.5 inhalation induced cardiac hypertrophy and fibrosis. FoxO1 might be a regulator of cardiac hypertrophy after PM2.5 exposure. Cardiac fibrosis induced by PM2.5 might be linked with macrophage activation.